Kepemimpinan Religius untuk Meningkatkan Moral Etika di Kabupaten Ponorogo - Near Anggreini Hesti Noviana (Journal of Islamic Economics (JoIE), 2024)
Introduction: Government leaders have not fully integrated religious values into their vision, mission, and work programs. This creates a gap between the nation's ideological values and the implementation of public policies, potentially leading to disorientation in national development goals. The absence of religious values in government policies can weaken the moral and ethical foundation that should guide strategic decision-making processes. Research Method: This study employs a qualitative descriptive approach to provide an in-depth analysis of the religious leadership style of Ponorogo Regent Sugiri Sancoko during the 2021-2024 period. The research focuses on understanding how religious values are reflected in government policies and leadership strategies. Result: Under Sugiri Sancoko’s leadership, policies were implemented to nurture future leaders with not only academic excellence but also noble character through the issuance of regional regulations (Perbup). Religious leadership strengthens moral and ethical values, forming a foundation for character education that fosters both academic and moral excellence in the younger generation. Conclusion: Religious leadership can enhance public trust by reinforcing moral and ethical principles in governance. This leadership style helps shape a generation with strong character and integrity, aligning governmental policies with ethical values that promote sustainable national development.